Atmospheric impurities enriching in Antarctic ice and changing of halogen biogeochemical cycles under the action of natural and anthropogenic factors - Bogillo, V. I.; Borchers, R.; Bazylevska, M. S. (Ukrainian Antarctic Journal, 2004)
An approach has been developed to estimate the atmospheric mixing ratio of atmospheric volatile impurities in ice samples taking into account their solubility in infiltrated water or in liquid-like surface layers on the snow grains. The ranges for the ratio were been calculated for all volatile species identified in 12 ice blocks sampled along profile of retreated Antarctic coastal glacier (Galindez Island, Argentinean Archipelago, West Antarctica). The age of these blocks is varied from 12 to 4000 years. The natural origin of CH3Cl, CH3CH2Cl, CH2=CHCl, CH3Br, CHBr3, CH3I, CH3CH2I, COS and CS2 in the pre-industrial atmosphere were confirmed whereas chlorofluorocarbons, hydrochlorofluorocarbons and chlorinated solvents (CCl4, CH2Cl2, CHCl3, CH3CCl3 and Cl2C=CCl2) have not essential natural sources in Antarctic environment. The identified natural Cl- and Br-consisting halocarbons have been responsible for 40% stratospheric ozone depletion over Antarctica during australian spring. The calculations were performed using mass-balance multimedia model to estimate effect of temperature and metamorphism of the snow cover on ratio between adsorbed and dissolved amounts, the fluxes in air and aqueous compartments of the cover and fate of the volatile impurities in all compartments of the snow pack. All these parameters possess the high sensitivity towards seasonal and daily temperature variations, snow metamorphism and to partitioning parameters of the impurities. The role of retreated coastal Antarctic glaciers as source of secondary emission of S- and halogen-containing atmospheric impurities into air and Southern Ocean during current global warming was discussed. It was estimated that up to 840 t COS, 54 t CS2, 50 t CH3Cl, 25 t CHBr3, 20 t CH2=CHCl, 14 t CF2Cl2, 10 t CFCl3, 16 t CH3I, 3 t Cl2C=CCl2 and 2,5 t CH3Br per year are to be released into the Antarctic environment during the calving of the icebergs and melting of the glaciers. The anthropogenic emission of chlorofluorocarbons, hydrochlorofluorocarbons and chlorinated solvents affects considerably on the biogeochemical cycles of the halogens. The stratospheric and tropospheric degradation of the halocarbons and their fate in the oceanic water and soils gives up to additional 5×106 t HCl per year. Also, lesser amount of HF is formed during stratospheric degradation of the chlorofluorocarbons and hydrochlorofluorocarbons. This creates the acidification of background wet depositions and leads to redistribution and accumulation of nssCl- and nssF- in polar regions.